2015
DOI: 10.3389/fmicb.2015.01158
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity of culturable fungi in the Heshang Cave, central China

Abstract: Caves are nutrient-limited and dark subterranean ecosystems. To date, attention has been focused on geological research of caves in China, whilst indigenous microbial diversity has been insufficiently characterized. Here, we report the fungal diversity in the pristine, oligotrophic, karst Heshang Cave, central China, using a culture-dependent method coupled with the analysis of the fungal rRNA-ITS gene sequences. A total of 194 isolates were obtained with six different media from 14 sampling sites of sediments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 55 publications
5
35
0
2
Order By: Relevance
“…The endophytic fungi were separated and purified following the methods reported [23]. The samples were washed repeatedly under running tap water, removing the surface soil and appendages.…”
Section: Separation and Purification Of Culturable Endophytic Fungimentioning
confidence: 99%
“…The endophytic fungi were separated and purified following the methods reported [23]. The samples were washed repeatedly under running tap water, removing the surface soil and appendages.…”
Section: Separation and Purification Of Culturable Endophytic Fungimentioning
confidence: 99%
“…Taking their similarities to sequences in GenBank, we identified 5 species: Readeriella eucalypti, Cladosporium pseudocladosporioides, Aspergillus wentii, Penicillium brevicompactum, Amphicorda felina (= Isaria felina = Beauveria felina). Man et al (2015) studying the phylogenetic diversity of culturable fungi in the Heshang Cave (China) reported that the genus Penicillium was the most abundant and accounted for 40, 54, and 52% of cultivable fungi in the sediments, weathered rocks and bat guano, respectively. Some other abundant fungal genera were Trichoderma, Paecilomyces, and Aspergillus, but in weathered rocks the presence of Cladosporium and Beauveria felina were also significant.…”
Section: Mycobiota Diversitymentioning
confidence: 99%
“…To test the hypothesis, we investigated the correlation between environmental factors, especially pH, and microbial communities in a full karst ecosystem, from the surface soils overlying the cave system and from various habitats within the cave, including epikarstic drip waters that link the surface to subsurface ( Figure 1B ). Although microbial communities have been separately investigated from drip waters in caves (Liu et al, 2010; Yun et al, 2016), cave sediments (Man et al, 2015; Wu et al, 2015), weathered rocks in caves (Ward et al, 2009; Man et al, 2015), soils overlying cave systems (Castro et al, 2010; Ortiz et al, 2014), and bat guano (Man et al, 2015), no systematic evaluation of the communities throughout a karst system has been conducted previously. The results from this study provide an assessment of bacterial communities in central China karst and reveal the potential consequence of acidification on bacterial community composition in the karst habitats.…”
Section: Introductionmentioning
confidence: 99%